2016
DOI: 10.1038/cddis.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

AIMP1 downregulation restores chondrogenic characteristics of dedifferentiated/degenerated chondrocytes by enhancing TGF-β signal

Abstract: Dedifferentiation and degeneration of chondrocytes critically influences the efficiency of cartilage repair. One of the causes is the defect of transforming growth factor (TGF)-β signaling that promotes chondrogenic differentiation and degeneration. In the present study, we found that aminoacyl-tRNA synthetase-interacting multifunctional protein 1 (AIMP1) negatively regulates TGF-β signaling via interactions with Smad2 and Smad3 in immunoprecipitation assay and luciferase assay. In addition, we observed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…The genes AIMP1, TBCK, NPNT, INTS12, HAS2 and ICMT, could be related to muscle development, cellular and organs growth. The AIMP1 gene and TBCK, act potentially over the muscle tissues and cartilage development (AHN et al, 2016;ZHU et al, 2009), and in the actin organization, cell growth, and proliferation (LIU et al, 2013), respectively. The NPNT and INTS12 genes could be related to organs growth and regulation during gestation until birth (OBEIDAT et al, 2013;SUN et al, 2018).…”
Section: Additive Direct Genetic Effectmentioning
confidence: 99%
“…The genes AIMP1, TBCK, NPNT, INTS12, HAS2 and ICMT, could be related to muscle development, cellular and organs growth. The AIMP1 gene and TBCK, act potentially over the muscle tissues and cartilage development (AHN et al, 2016;ZHU et al, 2009), and in the actin organization, cell growth, and proliferation (LIU et al, 2013), respectively. The NPNT and INTS12 genes could be related to organs growth and regulation during gestation until birth (OBEIDAT et al, 2013;SUN et al, 2018).…”
Section: Additive Direct Genetic Effectmentioning
confidence: 99%
“…Nevertheless, increasing evidence strongly suggests that the silencing of key anti-chondrogenic regulators may be effectively employed to enhance or even induce chondrogenesis, stimulate the production of cartilage matrix, and improve or stabilize the chondrocytic phenotype [21][22][23][24].…”
Section: Gene Silencing For Chondrogenesis: Potentialities and Challementioning
confidence: 99%
“…Enhanced cartilage tissue formation in vivo [23] ANGPTL4 Lipid metabolism Increased expression of collagen II and aggrecan, and suppression of MMP1, 3 and 13 in hMSCs [37] A. Lolli et al and help to preserve the integrity of articular cartilage.…”
Section: Aimp1 Angiogenesis and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, accumulating evidence has identified that AIMPs participate in various physiological and pathological processes as multifaceted molecules 10 13 . It was reported that the downregulation of AIMP1 enhanced transforming growth factor-β (TGF-β) signal by inducing the phosphorylation of Smad family member 2/3 (Smad2/3), which in turn promoted the chondrogenic potential of dedifferentiated/degenerated chondrocytes 14 . Furthermore, patients with a homozygous c.105C>A (p.Tyr35Ter) mutation in AIMP2 showed microcephaly, seizures, mental retardation, and spastic quadriplegia 15 .…”
Section: Introductionmentioning
confidence: 99%